End-of-life care: ‘Do not resuscitate’, ‘Do not intubate’ and ‘Allow natural death’: Ethical Dilemmas (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
One of the critical choices that a patient or their legal guardian may have to make after knowing that comfort is now the goal of care is whether or not there should be any attempts to revive their patient if and when the vital organs stops. As the ‘do not resuscitate’ (DNR), ‘do not intubate (DNI)’ and ‘allow natural death (AND)’discussion involves communications and other ethical matters; this review paper explored the different ethical issues and its practical applicability of these issues in the Indian context.
Keywords: Barriers; Cardiopulmonary resuscitation; Informed consent